Quality assessment of some bottled water produced in Okitipupa, Ondo state, Nigeria - Femi Adekunle, Folorunso; Aderonke Similoluwa, Folorunso; Abel Kolawole, Oyebamiji; Sunday Adewale, Akintelu (Київський національний університет імені Тараса Шевченка, 2020)
The aim of this study was to assess the safety level of some bottled water produced in Okitipupa, Ondo State Nigeria. Several packs of bottled water were obtained from three different manufacturers. Some physicochemical parameters and heavy metals were investigated to assess the quality of the bottle water using standard methods. The results from the physicochemical parameters and heavy metals were in with World Health Organization (WHO) standard for drinking water when compared. This study confirmed that the analyzed bottled water has good quality. Therefore, these bottled water are said to be safe for drinking.
Keywords: physico-chemical parameters; heavy metals; bottled water; atomic absorption spectrophotometer